Effects of garlic consumption on physiological variables and performance during exercise in hypoxia - Morris, D. M.; Beloni, R. K.; Wheeler, H. E. (Applied Physiology, Nutrition, and Metabolism, 2013)
Exposure to hypoxia results in vasoconstriction of the pulmonary vasculature (HPV) leading to pulmonary hypertension (HPH) and reductions in blood oxygen saturation and exercise performance. Alleviation of HPV and HPH via vasodilators has been shown to improve blood oxygen saturation and exercise performance in hypoxia. Garlic has been shown to reduce HPV and HPH in rats and has been suggested to have ergogenic effects in hypoxic exercise. We compared the effects of 7 days of supplementation with garlic and placebo on peripheral blood pressures, blood oxygen saturation, heart rate, oxygen consumption, and time to exhaustion during a progressive exercise test to exhaustion in humans under hypoxia (PIO2 88 Torr). No significant differences were observed between treatments regarding oxygen consumption, exercise or resting peripheral blood pressures, blood oxygen saturation, heart rates, or exercise time to exhaustion. These results do not support garlic consumption as a method for improving peripheral blood pressure, maximal oxygen consumption, blood oxygen saturation, exercising heart rate, heart rate response, or exercise performance in hypoxia.